2014
DOI: 10.1016/j.gecco.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

From rainforest to oil palm plantations: Shifts in predator population and prey communities, but resistant interactions

Abstract: a b s t r a c tAnthropogenic habitat change can dramatically alter biotic communities in tropical landscapes. Species that persist in human dominated landscapes are therefore likely to modify the way they interact. Although human impacts on community composition are relatively well studied, changes in species interactions are less well documented. Here we assess how logging of rainforest and conversion to oil palm plantations affects the populations of the ant-specialist giant river toad (Phrynoidis juxtaspera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…For example, non-aposematic Rhinella alata frogs in Panama [48] and Phrynoidis juxtaspera in Borneo [49] consume larger ants in the leaf litter community. Importantly, in our study, frog preference for certain ant traits did not change with habitat, a pattern also known to occur in Borneo [49] . Therefore, it is unlikely that poison frogs select for ants solely based on their chemical defenses.…”
Section: Poison Frogs Eat a Distinct Set Of Leaf Litter Faunamentioning
confidence: 99%
“…For example, non-aposematic Rhinella alata frogs in Panama [48] and Phrynoidis juxtaspera in Borneo [49] consume larger ants in the leaf litter community. Importantly, in our study, frog preference for certain ant traits did not change with habitat, a pattern also known to occur in Borneo [49] . Therefore, it is unlikely that poison frogs select for ants solely based on their chemical defenses.…”
Section: Poison Frogs Eat a Distinct Set Of Leaf Litter Faunamentioning
confidence: 99%
“…It has been suggested that functional diversity at different trophic levels can be retained in selectively logged forest (Barnes et al, 2014;Konopik, Gray, Grafe, Steffan-Dewenter, & Fayle, 2014) and that degraded forests remain of surprisingly high ecological value. Given that on a global scale, human-modified forests dominate over pristine forests Laurance et al, 2014), we urgently need to improve understanding of these land use changes on key ecological processes such as litter decomposition and soil nutrient cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Formicine ants are 389 known to be capable of differentiating between colors (Camlitepe and Aksoy, 2010) and do not 390 like strong colors (Science Buddies, 2011). It is possible that the dark brown color of the 0.10% 391 Arabica matched the appearance of potential predators i.e., Anoplolepis gracilipes-a predator 392 (Konopik, et al, 2014) an experiment, worked with the black crazy ant exposed its workers to four extracts of tea with 399 different sugar contents and found a significantly greater preference for two sweetest meals over 400 those without sugar or with the least amount of sugar. In related work, Stanley and Robinson 401 (2007), when dealing with Paratrechina bourbonica exposed its workers to five baits and 402 reported sugared solutions among the most attractive baits.…”
Section: Behavioral Responses Following Arabica Exposure At Sugar Conmentioning
confidence: 99%